Accounting Treatment For Venture Capitals : A Perception Of Venture Capital Companies In Malaysia - MOHD FARUK, FADZILLAH (2004)
This paper attempts to (1) explore the history and development of venture capitalists in Malaysia, (2) compare and contrast the various accounting standards for venture capital companies (VCCs) that are in existence locally and internationally, (3) examine the current accounting practice of VCCs, and (4) explore the perceptions of VCCs in Malaysia with regards to the new standard for consolidating accounts. From the existing various accounting standards, there is no specific accounting standard being issued by the Malaysian Accounting Standards Board (MASB), International Accounting Standards Board (IASB), Financial Accounting Standards Board (FASB) and Australian Accounting Standards Board (AASB) for VCCs. The accounting treatments of VCCs are covered under Business Combinations (FRS 3), Consolidated and Separate Financial Statements (FRS 127), Investments in Associates (FRS 128) and Interests in Joint Ventures (FRS 131). The new requirement of IAS 27 effectively changed the consolidation principles that existed for over 40 years.